Augmented Reality for Cognitive Screening in Neurodegenerative Diseases: A Ten-Year Systematic Review - Nascimento, Luiz Gustavo Guilherme do; Correia, Walter Franklin Marques; Campos, Fabio; Gisbergen, Marnix S. van; Barros, Marina de Lima Neves; Lins, Anthony; Teixeira, João Marcelo Xavier Natário (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Augmented Reality (AR) is increasingly explored as a low-burden alternative to pencil-and-paper cognitive tests for dementia and Parkinson’s Disease. Our objective with this review is to synthesize ten years (2014–2024) of empirical evidence on AR-based cognitive screening, estimate pooled diagnostic accuracy, and distil user-experience (UX) guidelines for people with neurodegenerative disorders. We searched Scopus with the string “augmented reality” AND cognitive AND (dementia OR Parkinson), screened 399 records, and retained 38 primary studies. Two reviewers independently extracted sample, task, hardware, and accuracy metrics. Optical see-through AR improved test sensitivity over matched non-immersive tests, while projection-based AR offered the largest UX gains. Hardware cost and eye-tracker drift were the main precision bottlenecks. AR can raise both diagnostic sensitivity and patient engagement, but only four studies used clinical-stage participants. Future work should couple low-cost hand-held AR with cloud inference to widen accessibility.